Kualitas Produk, Harga, Dan Kepuasan Pelanggan Dalam Mendorong Minat Beli Ulang - Fita Nurdiana; Eny Setyariningsih; Toto Heru Dwihandoko (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study's objective is to examine the influence of product quality (X1) and price (X2) on repurchase intention (Y), with customer satisfaction (Z) serving as an intervening variable at Om. Bean Café Mojokerto. A total of 200 respondents participated in this research, which employed a quantitative approach using questionnaires as the primary data collection instrument. The collected data were analyzed using the PLS 4 method. The findings reveal that all hypotheses are supported: customer satisfaction is significantly influenced by product quality, customer satisfaction is significantly influenced by price, repurchase intention is significantly influenced by product quality, repurchase intention is significantly influenced by price, and repurchase intention is significantly influenced by customer satisfaction. Furthermore, customer satisfaction was found to mediate the relationship between product quality and repurchase intention, as well as between price and repurchase intention. These results are expected to offer useful insights and strategic suggestions for café owners to enhance marketing effectiveness and strengthen customer loyalty in Mojokerto.